Phytochemical Analysis, Antioxidant Activity, and Cytotoxic Effects of Physalis angulata and Moringa oleifera Leaf Extracts on Cancer and Normal Cells In Vitro - Priyandoko, Didik; Widowati, Wahyu; Sholihah, Ika Adhani; Zahira, Nurul Zahra; Bangun, Adityana Arta; Kusdianti, Kusdianti; Hernawati, Hernawati; Surakusumah, Wahyu; Juansah, Rahadian Deden (UI Scholars Hub, 2024)
Physalis angulata and Moringa oleifera have long been the key ingredients of traditional medicine. This study aimed to obtain the metabolite profiles of the ethanolic leaf extracts of P. angulata (ELP) and M. oleifera (ELM), evaluate their antioxidant activity, and assess their toxicity against normal and cancer cells. The leaves were sourced from Balittro, West Java. The extraction used 70% ethanol and continued for 3 days. The metabolites were identified using Gas Chromatography-Mass Spectrometry (GC-MS), antioxidant activity was ascertained via the DPPH assay, and cytotoxicity was evaluated employing the PrestoBlue assay. GC-MS identified 23 compounds in ELP and 15 in ELM. The DPPH assay showed that ELM, ELP, or their combination exhibited marked antioxidant activity, with inhibition ranging from 50% to 90%. The toxicity assay against MCF-7 cancer cells demonstrated that ELP at 1,500 µg/mL and ELM at 1,200 µg/mL induced cytotoxicity. The ELP + ELM formulation exhibited stronger cytotoxic effects than the positive control. In contrast, ELM or ELP did not induce toxicity in normal CV-1 cells and, stimulated viability com-pared to the control. Thus, the phytochemical contents of ELM and ELP exhibited enhanced antioxidant activity, in-duced toxicity in cancer cells, and were safe for normal cells.